Penyusunan Laporan Keuangan Entitas Nonlaba Berdasarkan SAK Entitas Privat dengan Menggunakan Microsoft Excel - Armeliza, Diah; Khairunnisa, Hera; Arthawan, Ezzra (LPPM Universitas Negeri Jakarta, 2025)
The research is based by the importance of accountability in managing funds in non-profit organizations, as well as the low compliance of foundations in preparing financial reports in accordance with applicable standards. The results of observations conducted at the Taman Al Muhajirin 1407 Foundation show that the foundation only keeps simple financial records based on cash, without referring to the accounting principles set out in SAK EP. This research uses a qualitative approach with descriptive research methods and data collection techniques through interviews, observations, and document analysis. This research also uses the Research and Development (R&D) with ADDIE methods to compile guidlines fo using Microsoft Excel as a tool in preparing foundation financial reports. The results of this research indicate that the financial reports of the Taman Al Muhajirin 1407 Foundation can be prepared in accordance with SAK EP and presented in accordance with ISAK 335. The guidelines for using the Microsoft Excel program provide practical steps in preparing financial reports, so that the management of the Taman Al Muhajirin 1407 Foundation can prepare financial reports in accordance with SAK EP and ISAK 335 independently.